(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of hemostasis and the rate of complications associated with mechanical compression after transradial percutaneous coronary intervention (PCI-TRA) at the University Medical Center, Ho Chi Minh City and to explore related factors. Materials and Methods: A prospective descriptive study was conducted on 110 patients who underwent percutaneous coronary intervention via radial access between March 2025 and August 2025. Results: The hemostasis success rate was 94.6%. The mean compression duration until complete device removal was 5.42 ± 1.18 hours. Local complications were observed in 11.8% of cases (13/110), mainly hematomas (9.1%) and mild bleeding (5.5%). No cases of arteriovenous fistula or radial artery occlusion were recorded. Univariate analysis suggested that smoking, comorbidities, higher body mass index (BMI), larger sheath size, prolonged compression duration, and higher VAS scores were associated with the occurrence of complications. Conclusion: Mechanical compression using the Mostar device after PCI-TRA demonstrated a high rate of successful hemostasis with a low complication rate. Standardization of the stepwise decompression protocol and close monitoring of high-risk patients may help further reduce local complications.